2018
DOI: 10.1097/yco.0000000000000412
|View full text |Cite
|
Sign up to set email alerts
|

Ten-year evolution of suicide rates and economic indicators in large Brazilian urban centers

Abstract: The effect of economic indicators was heterogeneous among the centers, but, overall, the variation in suicide rates was inversely related to unemployment and did not show a significant relationship with GDP. These findings indicate a more complex link between economics and suicide whenever looking at local regional indicators. Further research should focus on possible intervening factors, what may inform better preventive interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
1
7

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 24 publications
0
15
1
7
Order By: Relevance
“…In this regard, Ahmadi et al (28) have reported financial problems as one of the major determinants and risk factors for SBs. Besides, other studies have shown a significant and positive relationship between financial problems, unemployment, and income level, and suicide (29,30).…”
Section: Discussionmentioning
confidence: 95%
“…In this regard, Ahmadi et al (28) have reported financial problems as one of the major determinants and risk factors for SBs. Besides, other studies have shown a significant and positive relationship between financial problems, unemployment, and income level, and suicide (29,30).…”
Section: Discussionmentioning
confidence: 95%
“…Suicide is a major global public health concern. It accounts for more than 800,000 deaths every year and is the second leading cause of death among people aged 15 to 29 years old 1,2. A total of 78% of suicides occur in low and middle-income countries 1.…”
Section: Introductionmentioning
confidence: 99%
“…Since 1985, as a result of decades of social and economic developments, Brazil’s epidemiological profile has been changing, contributing to a predominance of non-communicable diseases, especially in the most urbanized regions 4-6. According to the most recent census, there are 15 cities in Brazil with a population of over one million inhabitants 2,7. Although large cities can offer benefits in terms of social and economic development, individuals who live in large urban centers are also exposed to risks and hazards regarding physical and mental health problems 8…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Brazil, the WHO also indicated an increase in suicide rates among adolescents aged 15-19 years from 1990-2009 3 . Additionally, a study showed an increase in the age-adjusted suicide rate among adolescents of 9% between 2006 and 2015 4 . Moreover, another study showed that the suicide rate of adolescents increased by 24% in six large Brazilian cities and by 13% in the country between 2006 and 2015 5 .…”
Section: Introductionmentioning
confidence: 99%